Confocal micrographs: automated segmentation and quantitative shape analysis of neuronal cells treated with ostreolysin A/pleurotolysin B pore-forming complex. - Kopanja, Lazar; Kovacevic, Zorana; Tadic, Marin; Žužek, Monika Cecilija; Vrecl, Milka; Frangež, Robert (Histochemistry & Cell Biology, 2018)
Detailed shape analysis of cells is important to better understand the physiological mechanisms of toxins and determine their effects on cell morphology. This study aimed to develop a procedure for accurate morphological analysis of cell shape and use it as a tool to estimate toxin activity. With the aim of optimizing the method of cell morphology analysis, we determined the influence of ostreolysin A and pleurotolysin B complex (OlyA/PlyB) on the morphology of murine neuronal NG108-15 cells. A computational method was introduced and successfully applied to quantify morphological attributes of the NG108-15 cell line before and after 30 and 60 min exposure to OlyA/PlyB using confocal microscopy. The modified circularity measure C2n(S)<inline-graphic></inline-graphic> for shape analysis was applied, which defines the degree to which the shape of the neuron differs from a perfect circle. It enables better detection of small changes in the shape of cells, making the outcome easily detectable numerically. Additionally, we analyzed the influence of OlyA/PlyB on the cell area, allowing us to detect the cells with blebs. This is important because the formation of plasma membrane protrusions such as blebs often reflects cell injury that leads to necrotic cell death. In summary, we offer a novel analytical method of neuronal cell shape analysis and its correlation with the toxic effects of the pore-forming OlyA/PlyB toxin in situ.